Ścieżki jogi w Bhagawadgicie, czyli jedność w wielości - Jakubczak, Marzenna (Gajt Wydawnictwo 1991 s.c., 2018)
The paper aims at analysing the methods of spiritual growth, called the paths of Yoga, presented in Bhagavadgītā being a philosophical episode of Mahābhārata, the major Indian epic. It starts with a short characteristics of two most popular methodological perspectives used to read the Sanskrit text, namely diachronic and synchronic. The researchers who accept the first perspective stress incoherence of the Sanskrit work caused by its multilayer structure and a number of historical interpolations included in the course of the prolonged editorial process. Whereas the supporters of the synchronic reading strongly support the arguments in favour of consistence of the philosophical conception of self-development discussed in Bhagavadgītā. The author of the present paper, who argues for the later method, offers her reinterpretation of multiplicity of the yogic paths. In the subsequent sections of the paper concerning the leading paths of Yoga, she explains the specific stagesof the method suggested by Kṛṣṇa, including Sāṃkhya, Yoga, Karmayoga, Jñāyoga, Dhyānayoga and Bhaktiyoga. While doing so the author tries to justify the belief about the existence of a complex multistage Yoga method of self-development, which combines all other seemingly optional and rival methods that are ultimately subordinated to the highest instance: a cognitive insight (jñāna) or liberating spiritual wisdom (sthitaprajñā).
Keywords: Sāṁkhya